HEBB’S RULE DALAM PENGENALAN AKSARA TULAK-TULAK MANDAILING - Ridho, Abdurrahman; Suryadi, Suryadi; Andini, Mirna Ria (STMIK KAPUTAMA, 2021)
The use of artificial neural networks has now undergone a tremendous development. It is not limited only in the scope of computer mathematics but has reached several aspects of human life, such as health to art. At this time, the use of traditional languages is rarely used, especially in big cities where people are pluralistic. For this reason, the use of artificial neural networks to introduce computers with traditional letters needs to be done. This paper will discuss the use of the Hebb algorithm artificial neural network in recognizing tulak letters in the mandailing culture.